The relative role of IRAK-2 in TLR signalling - Flannery, Sinéad (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2012)
Toll-like receptors (TLRs) are pattern recognition receptors that recognise microbial ligands and subsequently trigger intracellular signalling pathways involving transcription factors such as NFkB and MAPKs such as p38. TLR signalling can regulate both transcriptional and post-transcriptional events leading to altered gene expression, and thus appropriate immune responses. The interleukin-1 receptor associated kinase (IRAK) family comprises four kinases that regulate TLR signalling. However, the role of IRAK-2 has remained unclear, especially in human cells. Recent studies using cells from inbred iRAK-2 -/- mice showed that murine IRAK-2 was not required for early TLR signalling events, but had a role in delayed NFkB activation and in cytokine production. IRAK-2 in mice has four splice variants, two of which are inhibitory, while human IRAK-2 has no splice variants.
Keywords: Biochemistry, Ph.D.; Ph.D. Trinity College Dublin.